2008
DOI: 10.2353/ajpath.2008.080358
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of JNK in ConA/GalN and ConA-Induced Liver Injury in Mice

Abstract: Tumor necrosis factor-␣-mediated liver injury can be induced by several different means; however, the signaling events and mechanisms of cell death are likely different. We investigated the mechanism of both apoptotic and necrotic hepatocyte cell death as well as the role of c-Jun

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 43 publications
7
34
0
Order By: Relevance
“…Previous work had indicated that liver injury induced by ConA alone was not primarily caused by a caspase-mediated apoptotic process (23,28). Consistently, caspase activation was not detected in either wild type or Bid-deficient livers 8 h after treatment when cellular injury was already apparent (Fig.…”
Section: And B)supporting
confidence: 57%
See 4 more Smart Citations
“…Previous work had indicated that liver injury induced by ConA alone was not primarily caused by a caspase-mediated apoptotic process (23,28). Consistently, caspase activation was not detected in either wild type or Bid-deficient livers 8 h after treatment when cellular injury was already apparent (Fig.…”
Section: And B)supporting
confidence: 57%
“…S1) or ConA/GalN-induced (23) hepatocyte apoptosis and liver injury. We also found that JNK1-deficient mice had similar phenotypes, although less significant than JNK2-deficient mice (23) (Fig. S1).…”
Section: And B)supporting
confidence: 48%
See 3 more Smart Citations